Multi-scale characterization of biomaterials using complementary X-ray and electron imaging techniques - Tedesco, James (My University, 2017)
Biomaterials may be any class of material that aids in the regeneration, replacement, or augmentation of damaged tissues. The design of biomaterials is becoming increasingly sophisticated as new technologies enable the manufacture and incorporation of smaller components and structural features. Thus, a demand for equally sophisticated tools and methods to study biomaterials are necessary. Two such tools are X-ray micro-computed tomography (micro-CT) and electron microscopy. Micro-CT has the advantage of imaging materials in 3D and non-destructively, but cannot reach the same resolving power as electron microscopy. However, electron microscopy has limited application with biomaterials due to destructive sample preparation requirements. The advantages and limitations of each imaging technique presents a complementary relationship between the two. This thesis aims to develop and apply a complementary workflow using X-ray and electron microscopy to investigate two diverse biomaterials: a titanium dental implant, and collagen tissue scaffold. In a pilot study, a 3D printed titanium dental implant with a novel dual-stemmed design was investigated for its biocompatibility in vivo. Dual-stemmed and conventional conical implants were inserted into the tibia of New Zealand White rabbits for 3 and 12 weeks, then retrieved with surrounding bone. The implants were analyzed using micro-CT, electron microscopy, and histology. Active bone growth and remodelling around the dual-stemmed implant at both time points was observed. Comparative bone-implant contact indicated the dual-stemmed implants supported bone-implant integration, and demonstrates the comparable biocompatibility of these 3D printed stemmed implants in rabbits up to 12 weeks. In a separate study, a gold functionalized collagen scaffold for tissue engineering applications has been developed. This scaffold design is intended for improved detection of scaffold degradation behaviour in vivo using X-ray CT. In this thesis, micro-CT and electron microscopy were used to analyze the resultant scaffold structure after fabrication, as it is important for understanding the outcomes of in vivo experiments. Imaging revealed a highly heterogeneous structure at both the micron and nanometer length scales. Interconnected pores from 50 – 400 μm made up 80% of the scaffold volume, while gold nanoparticles and agglomerates ranging from 16 – 1000 nm were non-uniformly dispersed at the nanoscale throughout the collagen matrix. This work highlights how complementary X-ray and electron microscopy can be applied to characterize diverse biomaterials during developmental and pre-clinical phases.
Keywords: biomaterials; x-ray; electron; imaging; microscopy; bone; collagen; gold nanoparticles; three dimensional; micro-CT; SEM; TEM; dental implant; scaffold; titanium; osseointegration; porosity